Pembangunan Pariwisata Berkelanjutan Pada Objek Wisata Desa Studi Kasus: Objek Wisata Embung Telaga Dapur Umum Desa Sukaraja Kecamatan Logas Tanah Darat Kabupaten Kuantan Singingi - Ruspianda, Riki; Yuliana, Dhina; Pratiwi, Retni; Karina, Rana (Dinamika Lingkungan Indonesia, 2025)
This research is Entitled Sustainable Tourism Development In Village Tourism Objects: A Case Study of Embung Telaga Dapur Umum Tourism Object in Sukaraja Village, Logas Tanah Darat District, Kuantan Singingi Regency." The research will be conducted over one year using a descriptive research method with a qualitative approach. The study aims to describe sustainable tourism development in village tourism objects. The urgency of this research lies in the fact that village tourism has become a strategic issue in achieving self-sufficient villages. Furthermore, each village is currently encouraged to explore its tourism potential. Therefore, the researcher is interested in studying this topic in the hope of assisting Sukaraja Village, Logas Tanah Darat District, in determining the direction for developing tourism objects in the village. The research findings indicate that sustainable tourism development in the Embung Telaga Dapur Umum tourism object can apply sustainable tourism development principles. This aligns with the principles of sustainable tourism object development, such as community participation, stakeholder involvement, the implementation of monitoring and evaluation, training for managers, optimal promotion, and accommodating community goals